Central giant cell granuloma in a paediatric maxilla: surgical management and a novel gene translocation. Issue 1 (January 2022) - Diab, Jason; Huang, Gwendolyn; Morrow, Rebecca; Moore, Lynette; Gue, Sam; Moore, Mark
Abstract: Central giant cell granuloma (CGCG) is a rare tumour. The aetiology remains controversial with immunohistological features suggestive of inflammatory, vascular and proliferative markers. It is most often diagnosed in children and young adults under the age of 30 years with a predilection for the mandible. We herein present a case in a paediatric age group of a maxillary lesion of CGCG with a novel genetic translocation. A combination of surgical intervention including enucleation and embolization produced a good result. The importance of long term follow up for facial growth and recurrence is terribly important for the child.